Catalytic and DFT study of selective ethylene oligomerization by nickel(II) oxime-based complexes - Tayade, Kamlesh N.; Mane, Manoj V.; Sen, Suman; Murthy, C. N.; Tembe, Gopal L.; Pillai, S. Muthukumaru; Vanka, Kumar; Mukherjee, Soumen (Journal of Molecular Catalysis A-Chemical, 2013)
The reactivity of nickel(II) thiophenealdoxime complex (3) toward oligomerization of ethylene in the presence of an alkylaluminum co-catalyst has been studied. The complex was found to be a selective ethylene dimerization catalyst in the presence of co-catalysts such as methylalumoxane (MAO) and diethylaluminum chloride (DEAC). With DEAC, the productivity was considerably higher than with MAO. Under optimum conditions the productivity reaches 388 kg/mol catalyst/h/bar with DEAC whereas for MAO this value was 119 kg/mol catalyst/h/bar. Complex 3 displays good ethylene conversions of up to a maximum of 90% with exceptionally high alpha-selectivity for 1-butene (>99.5%) amongst C-4 products. Computational studies using density functional theory (DFT) were also carried out to ascertain the decomposition pathway for 3 as well as that for Ni(II) complex of the pyridine ketoxime ligand 2. The results suggest that loss of one of the two bidentate oxime ligands attached to the metal center through reaction with DEAC is likely for both 2 and 3. Further, calculations indicate that the subsequent decomposition step was significantly more probable for 3 than for 2 thus explaining why the pyridine ketoxime ligand bound nickel complex 2 was experimentally found to be more stable than the thiophene aldoxime bound nickel complex 3. Calculations also show that the proton of the -OH group (oxime) plays a major role in the stability of the molecules. This was confirmed experimentally by synthesizing the Ni(II) dichloro complex of Pyridine-2-carbaldehyde O-methyloxime 5 and reacting it with ethylene under similar conditions. 5 was found to be highly active even at low co-catalyst concentrations. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Butene-1; Ethylene dimerization; Ni(II) complex; Thiophene aldoxime